The relationship between environmental exposures to pesticides measured by means of environmental exposure indices and the anthropomentric outcomes of boys living on farms in the rural Western Cape - Ochieng, Anne Achieng (Department of Public Health and Family Medicine, 2015)
Includes abstract.